2020
DOI: 10.3389/fphy.2020.585681
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical Oscillations in 2D Collective Cell Migration: The Elastic Turbulence

Abstract: Various types of mechanical waves, such as propagative waves and standing waves, are observed during 2D collective cell migration. Propagative waves are generated during monolayer free expansion, whereas standing waves are generated during swirling motion of a confluent monolayer. Significant attempts have been made to describe the main characteristics of mechanical waves obtained within various experimental systems. However, much less attention is paid to correlate the viscoelasticity with the generated oscil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
46
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 26 publications
(49 citation statements)
references
References 46 publications
3
46
0
Order By: Relevance
“…Notbohm et al (2016) considered 2D cell swirling motion within a confluent monolayer by monitoring the maximum radial velocity of . They reported that the long-time change of radial cell residual stress component correlated well with the long-time strain change during the time period of 24 h. This result points out to the Zener constitutive model, suitable for viscoelastic solid, which was elaborated rheologicaly by Pajic-Lijakovic and Milivojevic (2020c).…”
Section: Viscoelasticity Of Multicellular Systems For Various Regimesmentioning
confidence: 88%
See 4 more Smart Citations
“…Notbohm et al (2016) considered 2D cell swirling motion within a confluent monolayer by monitoring the maximum radial velocity of . They reported that the long-time change of radial cell residual stress component correlated well with the long-time strain change during the time period of 24 h. This result points out to the Zener constitutive model, suitable for viscoelastic solid, which was elaborated rheologicaly by Pajic-Lijakovic and Milivojevic (2020c).…”
Section: Viscoelasticity Of Multicellular Systems For Various Regimesmentioning
confidence: 88%
“…A long-time change of cell packing density was expressed by modifying the model proposed by Murray et al (1988): where τ is the long-time scale, is the flux of cells equal to , such that is the convective flux, is cell velocity, is the conductive flux, D eff is the effective diffusion coefficient, while are the sum of various fluxes such as haptotaxis, galvanotaxis, chemotaxis, durotaxis and plithotaxis (Murray et al, 1988; Pajic-Lijakovic and Milivojevic, 2020c). All mentioned fluxes influences the rate .…”
Section: Viscoelastic Regimes Change By Increase In Cell Packing Densitymentioning
confidence: 99%
See 3 more Smart Citations